Emotional attention for erotic stimuli: Cognitive and brain mechanisms. Issue 8 (11th August 2015) - Sennwald, Vanessa; Pool, Eva; Brosch, Tobias; Delplanque, Sylvain; Bianchi‐Demicheli, Francesco; Sander, David
ABSTRACT: It has long been posited that among emotional stimuli, only negative threatening information modulates early shifts of attention. However, in the last few decades there has been an increase in research showing that attention is also involuntarily oriented toward positive rewarding stimuli such as babies, food, and erotic information. Because reproduction‐related stimuli have some of the largest effects among positive stimuli on emotional attention, the present work reviews recent literature and proposes that the cognitive and cerebral mechanisms underlying the involuntarily attentional orientation toward threat‐related information are also sensitive to erotic information. More specifically, the recent research suggests that both types of information involuntarily orient attention due to their concern relevance and that the amygdala plays an important role in detecting concern‐relevant stimuli, thereby enhancing perceptual processing and influencing emotional attentional processes. J. Comp. Neurol. 524:1668–1675, 2016. © 2015 Wiley Periodicals, Inc. Abstract : We review recent literature showing that erotic stimuli involuntarily orient attention, and we propose possible cognitive and cerebral mechanisms underlying this process. Elucidating the mechanisms underlying attention orienting is important to understand how we can focus on the most relevant elements in the multifarious environment we live in.